Is terrestrial plant import from East Asia into countries in the EPPO region a potential pathway for new emerging invasive alien plants?. (26th June 2014) - van Valkenburg, J.; Brunel, S.; Brundu, G.; Ehret, P.; Follak, S.; Uludag, A.
Abstract : Pathway analysis represents an effective means of identifying emerging invasive alien species. For plants, a significant number of invasions have been caused by plant species originally voluntary introduced as ornamentals. The pathway analysis for terrestrial ornamental plants imported from East Asia has been undertaken to provide information on the imports and to identify emerging terrestrial invasive alien plants. Data for terrestrial ornamental plants imported from East Asia into Austria, France, Italy, the Netherlands and Turkey was assembled at the genus level. Thousands of species of plants for planting are imported from East Asia in very large volumes. However, despite the fact that the data could only been analyzed at the genus level, it is considered that only a very limited number of taxa would become invasive. The potentially invasive alien species are already widely available in European nurseries and are principally produced within the European Union.